Two German-Jewish rescue programmes launched in Great Britain, 1933–1939 - Rosner, Anna M. (European Spatial Research and Policy, 2021)
Between 1933 and 1939 many British organisations, as well as individuals, who witnessed the rise of Nazi Germany, the implementation of anti-Jewish laws, and growing anti-Semitism, decided to take action. There were numerous attempts aimed at supporting Jews living in the Third Reich, either by providing them with money or by helping them emigrate. This article describes two largest such programmes, i.e. the Kindertransports, and an unnamed action focused on intellectuals, scientists, and artists. The article first discusses the character of both, and then proceeds to explore the question of the character of the migrations presented, as well as the differences between migration and refuge seeking. It concludes with the issue of post-war mobility of the participants of both programmes.